Identifying Financial Distress Firms: A Case Study on Property and Real Estate Companies Listed In Indonesian Stock Exchange - Vaya Juliana Dillak; Zaza Humaida Fitri (Jurnal Manajemen Indonesia, 2019)
The objective of this study is to investigate the simultaneous and partial effects between ratio of liquidity, leverage, profitability and sales growth to financial distress in property companies listed in Indonesian Stock Exchange in 2013-2017. Sampling technique used in this study is purposive sampling technique. Sample in this study is as many as 38 samples within 5 years; therefore, a total of 190 company samples were obtained. Technique of analysis used in this study is logistic regression analysis using application of SPSS 24.0. Based on the research result, the ratio of liquidity, leverage, profitability and sales growth variables affect financial distress by 61.3%, and the rest of 38.7% is affected by other factors outside the research variables. Partially, liquidity variable has a positive effect to financial distress and profitability variable has a negative effect to financial distress. On the other hand, leverage variable proxied with debt to asset ratio and sales growth has no effect to financial distress.